Protein diffusion along DNA: on the effect of roadblocks and crowders. (17th November 2016) - Krepel, Dana; Levy, Yaakov
Abstract: Rapid recognition by a protein of its DNA target site is achieved through a combination of one- and three-dimensional (1D and 3D) diffusion, which allows efficient scanning of the many alternative sites. This facilitated diffusion mechanism is expected to be affected by cellular conditions, particularly crowding, given that up to 40% of the total cellular volume may by occupied by macromolecules. Both experimental and theoretical studies showed that crowding particles can enhance facilitated diffusion and accelerate search kinetics. This effect may originate from crowding forcing a trade-off between 3D and 1D diffusion. In this study, using coarse-grained molecular dynamic simulations, we investigate how the molecular properties of the crowders may modulate the effect exerted by crowding on a searcher protein. We show that crowders with an affinity to the DNA are less effective search facilitators than particles whose contribution is solely entropic. Crowders that have affinity to DNA may occupy DNA sites and thereby function as obstacles or roadblocks that slow down the searcher protein, and they may also produce a smaller excluded volume effect and so reduce usage of the hopping searching mode in favor of less-effective 3D diffusion in the bulk. We discuss how strong repulsive interactions between the crowding particles themselves may affect the overall dynamics of the crowders and their excluded volume effect. Our study shows that search kinetics and its mechanism are modulated not only by salt concentration and crowding occupancy, but also by the properties of the crowding particles.